ETIKA DIGITAL DALAM PERSPEKTIF GEREJA KATOLIK: TELAAH ATAS DOKUMEN ANTIQUA ET NOVA - Siapedeng, Nando; Wuritimur, Anastasia (Department of Theology - Sekolah Tinggi Filsafat Seminari Pineleng, 2025)
The rapid advancement of digital technology has transformed the way humans live, communicate, and form social relationships, while also presenting new ethical challenges that require responses from various parties, including faith communities. This article aims to examine the Catholic Church's perspective on digital ethics by critically reviewing the content of the document Antiqua et Nova, a contemporary moral reflection published by the Holy See. Through qualitative analysis of the document's content and Catholic moral principles such as human dignity, solidarity, subsidiarity, and the common good, it is found that Antiqua et Nova offers ethical guidance for the use of digital technology that is human-centered. This document emphasizes the importance of moral responsibility among digital users, as well as the need to build a communication culture based on truth, justice, and love. Furthermore, the reflections in this document are consistent with previous Church social teachings and relevant to.